2020
DOI: 10.1016/j.ajo.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Outcomes and Prognostic Factors of 23-Gauge Vitrectomy for Retained Lens Fragments After Phacoemulsification

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Timing of the IOL implantation (during primary phacoemulsification or during/after vitrectomy) and the type of IOL did not significantly impact final vision. This study showed that the results of the 23-gauge vitrectomy for retained lens fragments are similar to those of non-MIVS studies [10].…”
Section: Outcomes Of Vitrectomysupporting
confidence: 77%
See 1 more Smart Citation
“…Timing of the IOL implantation (during primary phacoemulsification or during/after vitrectomy) and the type of IOL did not significantly impact final vision. This study showed that the results of the 23-gauge vitrectomy for retained lens fragments are similar to those of non-MIVS studies [10].…”
Section: Outcomes Of Vitrectomysupporting
confidence: 77%
“…In the cases where the lens fragment is in the posterior segment, pars plana vitrectomy (PPV) remains the most effective strategy to remove the intravitreal material [10]. Prior to surgical treatment, concomitant issues of inflammation and increased intraocular pressure should be managed medically.…”
Section: Surgical Management Of Retained Lens Fragmentsmentioning
confidence: 99%
“…9 Paul et al and Chan et al reported more favorable outcomes in eyes with DLF, with 82.5% and 62.9% of the eyes achieving a Snellen VA of ≥20/40 at 3 and 6 months of followup, respectively. 16,17 It is of note that direct comparison of visual outcomes between studies is difficult because of variability in inclusion criteria, follow-up duration, and the nature of reporting.…”
Section: Discussionmentioning
confidence: 99%
“…8,15 The visual outcome and reported complication rates after managing eyes with DLF vary among reports. 9,11,[15][16][17] This can be attributed to the small sample sizes, the lack of distinction between PCR alone and PCR with DLF, and the variability of follow-up intervals used by different investigators.…”
mentioning
confidence: 99%
“…[ 3 , 4 ] A small minority of these eyes can be managed medically, but a pars plana vitrectomy (PPV) is still the gold standard for removing residual lens debris and reducing the risk of further complications. [ 4 , 5 ] As a result, the roles of both the cataract surgeon and the vitreoretinal (VR) surgeon are critical in the prevention and management of displaced lens fragments in the vitreous cavity.…”
mentioning
confidence: 99%